Salmonella enterica Typhimurium engineered for nontoxic systemic colonization of autochthonous tumors. (16th March 2021) - Augustin, Lance B.; Milbauer, Liming; Hastings, Sara E.; Leonard, Arnold S.; Saltzman, Daniel A.; Schottel, Janet L.
Abstract: Much of the bacterial anticancer therapy being developed relies on the ability of bacteria to specifically colonise tumours. Initial attempts to translate promising Salmonella enterica Typhimurium ( S . Typhimurium) preclinical results to the clinical setting failed, primarily due to lack of tumour colonisation and the significant toxicities from systemically administered Gram-negative bacteria. To address the difference in results between preclinical experiments performed in mice with transplant tumours and clinical trials in human volunteers with autochthonous tumours, a genetically engineered mouse model of breast cancer (BALB-neuT) was utilised to develop a strain of virulence-attenuated S . Typhimurium capable of robust colonisation of autochthonous tumours. Several genes that code for bacterial surface molecules, responsible for signalling a toxic immune response against the bacteria, were mutated. The resulting S. Typhimurium strain, BCT2, allowed non-toxic intravenous administration of 3 × 10 6 colony forming units of bacteria in tumour-burdened mice when combined with a vascular disruption agent to induce intratumoral necrotic space and facilitate bacterial colonisation.